Differences and diversity of autoimmune encephalitis in 77 cases from a single tertiary care center - Abhinbhen W. Saraya; Kanthita Worachotsueptrakun; Kritchai Vutipongsatorn; Chanikarn Sonpee; Thiravat Hemachudha (BMC Neurology, 2019)
Abstract Background The incidence of autoimmune encephalitis has risen globally. There are two general categories of disease-associated antibodies that can be tested for: neuronal surface and intracellular. However, testing both groups of autoantibodies are costly. This study aims to identify differences between groups by comparing clinical presentations, radiological findings and CSF profile of patients, and determine if any parameters are indicative of one group of autoantibodies over another. Additionally, we aim to report the local incidence of less common groups of disease-associated antibodies as well. Methods Seventy-seven records of autoimmune encephalitis/encephalomyelitis patients admitted to King Chulalongkorn Memorial Hospital, Bangkok, Thailand, between October 2010 and February 2017 were reviewed. Patients with infections or those with classic central nervous system demyelinating features were excluded. Results Of 77 patients, 40% presented with neuronal surface antibodies and 33% had intracellular antibodies. The most common autoantibody detected in each group was anti-NMDAr antibody (25/31, 81%) and anti-Ri antibody (7/25, 28%) respectively. In the neuronal surface antibody group, behavioral change was the most common complaint (45%), followed by seizures (39%) and abnormal movements (29%). In the latter group, seizure was the most common presenting symptom (32%), followed by motor weakness (20%), behavioural change (16%) and abnormal movements (16%). Patients with neuronal surface antibodies were younger (35 vs 48 years old, p = 0.04) and more likely to present with behavioral change (45% vs 16%, p = 0.02). Mortality rate was higher in the intracellular group (16% vs 3.2%, p = 0.09). No differences were detected in magnetic resonance imaging (MRI) and CSF profile. Conclusions In the early stages of the disease, both groups have comparable clinical outcomes. Although there were significant differences in age and percentage of patients with behavioral change, both groups of autoimmune encephalitis still shared many clinical features and could not be distinguished based on MRI and CSF profiles. Therefore, we recommend that patients with features of autoimmune encephalitis should be screened for both the neuronal surface and intracellular antibodies regardless of clinical presentation.